ANALISIS KESALAHAN SINTAKSIS DALAM BUKU TEKS BAHASA ARAB UNTUK PERGURUAN TINGGI KEAGAMAAN ISLAM - Suharto, Toto; Fauzi, Ahmad (Arabiyat : Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2017)
This article described that textbooks used in higher education as a part of the standards of learning material. The learning material did not meet the national standards of higher education if universities did not have a learning material in the form of textbook. One important aspect in writing a textbook was its compliance with grammar. This article attempted to analyze the syntactic errors contained in the textbook, al-Mahir al-Istima fi Tatbiq wa al-Kalam, published by Center of Language Development at IAIN Surakarta. The forms of syntactic errors and the correction of the errors were the focuses of this research. This study used the error analysis. The research found  that a syntactic error found in the reading passages were eight forms of errors in isim isyarah (the most one), na‘at-man‘ut, fa‘il, isim maushul, jawab syarat, khabar, ‘athaf-ma‘thuf, and na’ib al-fa‘il. Lastly, this textbook was therefore recommended to be revised.